Highly Sensitive Determination of Hg(II) Using Self-Assembled Monolayer of 4-Pyridineethanthiol on Gold Nanoparticles Modified-Glassy Carbon Electrode Pretreated by Exclusively Cathodic Polarization - Phong, P.H.; Anh, N.H.; Hung, L.Q.; Ha2, N.T.C.; Ha, V.T.T. (Asian Journal of Chemistry, 2013)
Modification of the glassy carbon electrode (GCE) with gold nanoparticles coated by 4-pyridineethanthiolate hydrochloride self-assembled monolayer for determination of Hg2+ by differential pulse voltammetry has been studied. Use of the exclusively cathodic polarization method at potential of -1.0 V to activate the GCE surface enhanced the sensitivity of the analysis compared with use of both anodic and cathodic polarizations or exclusive anodic polarization. The calibration curve for the differential pulse voltammetry peak current of Hg2+ versus its concentration showed two linear regions. The first region demonstrated linearity in the range from 5.0 × 10-11 to 5.0 × 10-9 M with a correlation coefficient of 0.993. The slope of the second linear region was smaller than the first region's slope with the linear range of 5.0 × 10-9-7.0 × 10-7 M (R2 = 0.998). The detection limit was 4.5 × 10-12 M estimated from three times the standard deviation of the background noise. The selectivity of the modified GCE for Hg2+ over other metals ions in aqueous solutions was remarkably high (at least 100-fold excess). The applicability of the modified GCE in determination of Hg2+ in real water samples without any pretreatment was successfully demonstrated.